Adolescents' use of social networking sites and parental monitoring - Manlantao, Maricel Oprenario
This study aims to enumerate social networking sites (SNS) joined by adolescents, identify the reasons for using SNS and the disadvantages of SNS, and describe the presence or absence of parental monitoring in adolescents' social networking. Survey and in-depth interviews were conducted in Ramon Magsaysay (Cubao) Cubao High School among 100 respondents and 20 participants respectively. Quota sampling for the survey and simple random sampling for the in-depth interview were used. Frequencies, percentages, and thematic tables were used to present and analyze data. Results show that the participants visit 13 SNS wherein Facebook (39%) and Friendster (35%) are the top two frequently visited. Communication (34%), Meet new friends (31%), and Entertainment (21%) are the top three reasons for joining SNS. The top three disadvantages include Academic problems (17%), Internet addiction (11%), and Health problems (85). Ways of parental monitoring include checking, limiting, asking, and keeping company. Basis for stating the absence of parental monitoring include freedom, not asked by parents, and parents are not around. Fifty one percent (51%) of parents monitor their children's SNS. Adolescents without personal monitoring consider freedom as both advantage and a disadvantage. Moreover, findings show that there is no association between parental monitoring and the places where adolescents access SNS. Inclusion of parents in the study, comparison, between parental and maternal monitoring and between urban and rural adolescents, and inclusion of factors like birth order, number of siblings, economic income, educational attainment of parents, and type of school, gender, and age of adolescents are recommended.